Immunophenotypic Diagnosis of Primary Cutaneous Lymphomas: A Review for the Practicing Dermatologist - Campbell, Shannon M. (Matrix Medical Communications, 2010)
The application of CD markers to medicine has advanced our understanding of several dermatological diseases, most notably primary cutaneous lymphomas. CD markers are monoclonal antibodies that target cell surface molecules on leukocytes and antigens from other cells. T-cell processes are typically CD3+, CD20-, CD45+ while B-cell processes are typically CD3-, CD20+, and CD45+. Other CD markers are used to further delineate cutaneous lymphomas. Although an imperfect system, CD markers empower dermatologists to synthesize immunophenotyping with clinical findings and formulate an appropriate diagnosis.